2003
DOI: 10.1074/jbc.m306920200
|View full text |Cite
|
Sign up to set email alerts
|

The Conversion of ApoB100 Low Density Lipoprotein/High Density Lipoprotein Particles to ApoB100 Very Low Density Lipoproteins in Response to Oleic Acid Occurs in the Endoplasmic Reticulum and Not in the Golgi in McA RH7777 Cells

Abstract: The site where bulk lipid is added to apoB100 low density lipoproteins (LDL)/high density lipoproteins (HDL) particles to form triglyceride-enriched very low density lipoproteins (VLDL) has not been identified definitively. We employed several strategies to address this question. First, McA RH7777 cells were pulse-labeled for 20 min with [35 S]methionine/cysteine and chased for 1 h (Chase I) to allow study of newly synthesized apoB100 LDL/HDL remaining in the endoplasmic reticulum (ER). After Chase I, cells we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 33 publications
0
37
0
Order By: Relevance
“…Scd-1 catalyses the desaturation of saturated fatty acyl-CoAs (for example, stearoyl-CoA) to monounsaturated fatty acyl-CoAs (for example, oleyl-CoA). Given that oleic acids promote the final steps of lipid-rich VLDL assembly and potentiate the secretion of VLDL-TG 49 , we postulate that an inhibition of scd-1, and the consequent reduction of oleyl-CoA availability and bulk lipid transfer to apoB-lipoproteins in the late stages of their assembly, underlies the MBH oleic acid-induced lowering of hepatic VLDL-TG secretion. Also, it remains a possibility that converging neuronal and hepatic metabolic pathways may mediate the ability of MBH fatty acid sensing to regulate hepatic lipid and glucose homeostasis.…”
Section: Discussionmentioning
confidence: 92%
“…Scd-1 catalyses the desaturation of saturated fatty acyl-CoAs (for example, stearoyl-CoA) to monounsaturated fatty acyl-CoAs (for example, oleyl-CoA). Given that oleic acids promote the final steps of lipid-rich VLDL assembly and potentiate the secretion of VLDL-TG 49 , we postulate that an inhibition of scd-1, and the consequent reduction of oleyl-CoA availability and bulk lipid transfer to apoB-lipoproteins in the late stages of their assembly, underlies the MBH oleic acid-induced lowering of hepatic VLDL-TG secretion. Also, it remains a possibility that converging neuronal and hepatic metabolic pathways may mediate the ability of MBH fatty acid sensing to regulate hepatic lipid and glucose homeostasis.…”
Section: Discussionmentioning
confidence: 92%
“…Our studies raise the possibility that apoA-IV may function as a modulatory cofactor to reduce apoB's rate of intracellular transport, thereby increasing its residence time within a lipoprotein expansion compartment. The exact intracellular compartments involved in second step expansion are under active investigation but appear to involve the ER (25,46) and/or Golgi (47)(48)(49). Because the capacity to enlarge nascent lipoproteins is the predominant means by which the intestine accommodates increased lipid flux, apoA-IV, via its trafficking effects on apoB, may play an important role in this process, particularly under conditions of high dietary fat intake.…”
Section: Discussionmentioning
confidence: 99%
“…Using this system, we observed that although transfection of apoA-IV-KDEL and native apoA-IV both reduced the secretory effi ciency of apoB relative to control cells, apoA-IV-KDEL markedly inhibited cellular TG secretion, whereas native apoA-IV increased TG secretion into media, the association of apoB with d < 1.006 g/ml lipoproteins, and the diameter of VLDL 1 particles. Considered together, these data suggest that apoA-IV may act as a chaperone that modulates the traffi cking of apoB through the secretory pathway, thereby prolonging the residence time of nascent apoB-containing particles in cellular compartments where lipidation occurs ( 13,14,16,46 ), enhancing TG loading and, ultimately, increasing TG secretion.…”
Section: S]met Andmentioning
confidence: 93%